Riba dalam Perspektif al-Qur’an dan Sunnah - Muhamad Zainul Abidin (LPPM IAIT, 2022)
This study tries to find information related to usury holistically and comprehensively based on the verses of the Qur'an and the traditions of the Prophet, by conducting a thematic study to obtain authentic and in-depth information. So it is hoped that with the results of this research, the community, especially Muslims in Indonesia, will get a correct and comprehensive knowledge and understanding of usury. This research is library research using the maudhu'i interpretation and takhrij hadith methods. The maudhu'i interpretation method is used to explore in-depth and holistic information from the Qur'an. While the takhrij hadith method is used to obtain valid and comprehensive information from the hadith. Based on the results of the study, the key that the scholars are that usury is unlawful, including major sins whose perpetrators are threatened by Allah with severe punishment and punishment. The prohibition of usury is based on three main arguments that have the highest authority in Islamic law, namely the Qur'an, as-Sunnah, and Ijma'. The prohibition of usury is comprehensive. This means that all forms of usury are haraam, either a little or a lot.